2019
DOI: 10.1039/c9tx00080a
|View full text |Cite
|
Sign up to set email alerts
|

Prometryn induces apoptotic cell death through cell cycle arrest and oxidative DNA damage

Abstract: Prometryn is a slightly to moderately toxic herbicide belonging to the triazine family of herbicides, which are widely used in agriculture to control the growth of various weeds. Although many studies have shown that triazine herbicides have carcinogenic potential in humans, the cytotoxic effects of prometryn on human cells, and the mechanisms underlying these effects, are not yet fully understood. The lung is one of the most important organs where there is accumulation of environmental pollutants. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Additionally, DNA damage is closely associated with cell cycle alterations in mammalian cells [ 25 , 26 ]. Hence, we evaluated the effects of PM 2.5 on cell cycle alterations in HaCaT keratinocytes using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, DNA damage is closely associated with cell cycle alterations in mammalian cells [ 25 , 26 ]. Hence, we evaluated the effects of PM 2.5 on cell cycle alterations in HaCaT keratinocytes using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Triazine concentrations of up to 108 μ g/L have been reported in North America rivers [ 15 ]. In addition, all triazine herbicides and their degradation products are persistent in the environment, especially in air and water, and these pesticides can damage human cardiac and immune systems and endanger the health of humans, animals, and plants [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that bufalin can significantly inhibit the proliferation and colony formation of U251 cells and cause structural loss of mitochondria and endoplasmic reticulum in these cells. The S-phase checkpoint is one of the important mechanisms of DNA damage repair, as this machinery senses whether the DNA of a cell is damaged and whether damaged DNA is repaired, thereby preventing damaged DNA from being replicated and passed down to daughter cells [ 21 23 ]. The results of our qRT-PCR experiments showed that the mRNA expression levels of Chk1, ATR, CDC25A and CDK2 in U251 cells treated with bufalin were significantly upregulated, and the ATR-Chk1-CDC25A-CDK2 pathway was activated to transmit DNA damage signals, which directly caused U251 cell cycle arrest in the S phase.…”
Section: Discussionmentioning
confidence: 99%